Leprosy in post-elimination era in India: Difficult journey ahead - Archana Singal; Sidharth Sonthalia (Wolters Kluwer Medknow Publications, 2013)
Leprosy is a chronic inflammatory disease of skin and peripheral nerves. Elimination of leprosy as a public health problem was reached at the global level in the year 2000 and by India on 31 st December, 2005. Thereafter, leprosy services in India have been integrated with General Health-Care System resulting in reduced focus and funds. Sustaining the gains made so far in controlling leprosy is a big challenge and there is no time for complacency. Pockets of high endemicity with prevalence rate of > 1 still exist in many states. Our data from a tertiary care center indicates poor epidemiological control and ongoing disease transmission. To combat this, dermatologists all over India should continue to play a central role in capacity building and training of undergraduate and post-graduate students, medical officers, and field workers.